Penentuan Parameter Proses Laser Cutting Terhadap Kekasaran Permukaan Material Acrylyc - Muhammad Sobron Yamin Lubis; Agasha Wiyoso; Harry Wibowo; Silvi Ariyanti (CV. IRA PUBLISHING, 2023)
Cutting materials using a laser beam is one of the modern methods in machining processes to cut complex geometries in two dimensions using a laser beam. Laser cutting can be used in cutting acrylic materials. However, there are obstacles to producing good surface conditions. The use of appropriate process parameters dramatically affects the resulting surface roughness. Therefore, it is necessary to research to determine the parameters of the laser cutting process that are suitable for the surface conditions of the workpiece, which has a small surface roughness value. Three variations of process parameters were used, namely cutting speeds of 6, 8, and 10 (mm/s), laser focus points of 4,6,8 (mm), and gas pressures of 90, 100, and 110 (mm/s). The specimens that have been cut then measured the surface roughness using a surface test measuring tool. The measurement data is then analyzed using the Taguchi method. The results showed that the highest roughness value was found in the second experiment with a roughness value of 1.015 µm, and the lowest was in the seventh experiment with a roughness value of 0.225. To produce a small roughness value, the process parameters used are gas pressure 100 mm/s, cutting speed eight mm/s and focal point 8 mm/s, and the most dominant influence factor is the gas pressure parameter with a value of 7.494.